2016
DOI: 10.4103/2277-9175.182215
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet-rich plasma compared with whole blood for the treatment of chronic plantar fasciitis; a comparative clinical trial

Abstract: Background:Intralesional injection of autologous blood-derived products has recently gained attention as a potential treatment for plantar fasciitis (PF). We compared platelet-rich plasma (PRP) and whole blood (WB) for the treatment of chronic PF.Materials and Methods:Patients with chronic PF received either an intralesional injection of 3 cc PRP prepared by double centrifuge technique or WB (n = 17 in each group). Overall, morning and walking pain severity were assessed by 11-point numerical rating scale, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Three studies reported the data of RMS. [ 21 , 23 , 26 ] Pooled estimate suggested that, PRP had a comparable effect with other treatments in the change from baseline in RMS (WMD = −0.34, 95% CI: −1.04, 0.35; P = .334) (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Three studies reported the data of RMS. [ 21 , 23 , 26 ] Pooled estimate suggested that, PRP had a comparable effect with other treatments in the change from baseline in RMS (WMD = −0.34, 95% CI: −1.04, 0.35; P = .334) (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 91%
“…The sample size of these studies ranged from 28 to 60 (total 445, 128 males and 317 females). Among the included studies, 2 were conducted in India, [ 22 , 24 ] 2 in Iran [ 23 , 26 ] and Egypt, [ 29 , 30 ] each one in UK, [ 21 ] Mexio, [ 25 ] Turkey, [ 27 ] and USA. [ 28 ] Nine trials compared the effects of PRP with steroid, [ 21 , 22 , 24 , 25 , 27 30 ] and one compared PRP with whole blood.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review identified three randomized trials, all showing promising results [78]. However, a very small trial challenged this method of plasma preparation, as the same clinical effectivity was observed after the injection of whole blood [79]. Different surgical approaches have been developed.…”
Section: Comparison Of Ld-ebrt With Other Therapiesmentioning
confidence: 99%